2022
DOI: 10.1016/j.isci.2022.103741
|View full text |Cite
|
Sign up to set email alerts
|

Potential greenhouse gas risk led by renewable energy crowding out nuclear power

Abstract: Summary Increasing variable renewable energy (VRE) is one of the main approaches for greenhouse gas (GHG) mitigation. However, we find a GHG increase risk associated with increasing VRE: VRE crowds out nuclear power (VRECON) but cannot fully obtain the left market share, which is obtained by fossil energy. We developed an integrated dispatch-and-investment model to estimate the VRECON GHG-boosting effect in the Pennsylvania-New Jersey-Maryland Interconnection and the Electric Reliability Council of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…However, RES shows a negative mediation effect, suggesting that the RES spurred by REPs may increase carbon emissions. Existing research attributes the carbon‐increasing effects of RED to a surge in energy consumption during the early stages of RED (Kabeyi & Olanrewaju, 2022), the crowding out effect on other clean energy sources like nuclear power (X. Zhao et al., 2022), the absence of storage technologies addressing intermittent supply issues (Qudrat‐Ullah, 2022), and additional FE consumption to meet peak load requirements (Apergis et al., 2010). Nevertheless, current studies have overlooked some other critical factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, RES shows a negative mediation effect, suggesting that the RES spurred by REPs may increase carbon emissions. Existing research attributes the carbon‐increasing effects of RED to a surge in energy consumption during the early stages of RED (Kabeyi & Olanrewaju, 2022), the crowding out effect on other clean energy sources like nuclear power (X. Zhao et al., 2022), the absence of storage technologies addressing intermittent supply issues (Qudrat‐Ullah, 2022), and additional FE consumption to meet peak load requirements (Apergis et al., 2010). Nevertheless, current studies have overlooked some other critical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nuclear energy, as a low-carbon energy source, can provide an ideal combination of energy (i.e. heat, electrons and radiation) to meet activation and/or CO2 conversion requirements [4].…”
Section: Co2 Emissions From Nuclear Power Plantsmentioning
confidence: 99%
“…They also found that renewable energy policies could play a vital role in achieving China’s carbon peak goal before 2030, such as carbon market [ 19 , 20 ], reduction in fossil-fuel subsidies [ 21 , 22 , 23 ], electricity market reform [ 17 , 24 , 25 ], renewable energy portfolio standards [ 26 , 27 ], and mix of other policies [ 28 , 29 ]. Nevertheless, several recent studies have found that current renewable energy policies are not able to abate CO 2 emissions effectively [ 30 , 31 , 32 ]. For example, Guo et al (2021) found that the improvement of renewable energy technologies could not prevent carbon emissions from continuously increasing toward 2030, and the carbon peak goal may not be realized [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al (2021) also suggested that the single policy of the carbon market could not achieve the carbon neutrality goal, and more ambitious policies are needed, such as rapid electrification and deep economic transformation [ 31 ]. Furthermore, Zhao and Zhong et al (2022) even found that the incremental consumption of renewable energy would increase carbon emissions, as the development of renewable energy may crowd out nuclear power and increase the peak-shaving demand for fossil-fired electricity [ 32 ]. Furthermore, to our knowledge, previous studies have not explicitly examined and compared the effectiveness of different renewable energy policies in achieving China’s carbon neutrality goals.…”
Section: Introductionmentioning
confidence: 99%